Facts about Vitamin D - Linda B. Bobroff; Isabel Valentín-Oquendo (EDIS)
Revised! FCS-8640, a 2-page illustrated fact sheet by Linda B. Bobroff and Isabel Valentín-Oquendo, summarizes key facts about vitamin D’s role in human nutrition — why we need it, what happens if we don’t get enough, how much we need, how we can get enough, supplements, and how much is too much. Includes links to reliable nutrition information on the internet. Published by the UF Department of Family Youth and Community Sciences, April 2009.